Perspectives on the complex links between depression and dementia - Hakim, Antoine (Frontiers in Aging Neuroscience, 2022)
This review highlights that depression is a growing health problem for the individual, and because of its high frequency in most societies, a growing burden on health care budgets. The focus of the review is the physiological links between depression and dementia, specifically Alzheimer's disease. It suggests that depression is a significant risk factor for cognitive decline and explores the pathways that may lead depressed individuals to suffer this outcome. This review shows that depression and a number of its precursors activate pro-inflammatory mediators. These lead to cerebral small vessel disease with the consequent reduction in cerebral blood flow, which is known to precede cognitive decline. Thus, the impact of depression on the physiological events that lead to dementia is identical to the impact of other dementia risk factors recently reviewed1. Depression is distinct however in being a relatively treatable condition, but the impact of treating depression on later cognitive decline is not always positive, leading to the hypothesis that only the antidepressants that attenuate inflammation alleviate subsequent cognitive decline.